Identification of novel FBN1 variations implicated in congenital scoliosis - Lin, Mao; Zhao, Sen; Liu, Gang; Huang, Yingzhao; Yu, Chenxi; Zhao, Yanxue; Wang, Lianlei; Zhang, Yuanqiang; Yan, Zihui; Wang, Shengru; Liu, Sen; Liu, Jiaqi; et al. (Journal of human genetics, 2020)
Congenital scoliosis (CS) is a form of scoliosis caused by congenital vertebral malformations. Genetic predisposition has been demonstrated in CS. We previously reported that TBX6 loss-of-function causes CS in a compound heterozygous model; however, this model can explain only 10% of CS. Many monogenic and polygenic CS genes remain to be elucidated. In this study, we analyzed exome sequencing (ES) data of 615 Chinese CS from the Deciphering Disorders Involving Scoliosis and COmorbidities (DISCO) project. Cosegregation studies for 103 familial CS identified a novel heterozygous nonsense variant, c.2649G>A (p.Trp883Ter) in FBN1 . The association between FBN1 and CS was then analyzed by extracting FBN1 variants from ES data of 574 sporadic CS and 828 controls; 30 novel variants were identified and prioritized for further analyses. A mutational burden test showed that the deleterious FBN1 variants were significantly enriched in CS subjects (OR = 3.9, P = 0.03 by Fisher’s exact test). One missense variant, c.2613A>C (p.Leu871Phe) was recurrent in two unrelated CS subjects, and in vitro functional experiments for the variant suggest that FBN1 may contribute to CS by upregulating the transforming growth factor beta (TGF-β) signaling. Our study expanded the phenotypic spectrum of FBN1 , and provided nove insights into the genetic etiology of CS.